Geothermal exploitation well cement composite admixture and preparation method thereof
Patent Information
- Application Number
- CN202610957930.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-16
AI Technical Summary
[0002]当前干热岩地热开采的核心技术是CO2-EGS,以超临界CO2为换热介质,相比传统水介质换热效率大幅度提升,但其固井水泥环长期服役于高温高压、地热流体冲刷的极端工况,传统固井水泥在此环境下易发生碳化腐蚀,致水泥石孔隙率升高、强度倒缩、渗透率大幅上升
1.本发明采用多尺度协同抗CO2腐蚀的整体机制,突破传统单一材料耐蚀材料的性能局限,最终制得拥有优异的抗CO2腐蚀特性的材料。使用固废作为主要原材料,既缓解了固废排放带来的环境压力,也进一步压低了材料成本;同时通过引入改性铝硅酸盐空心陶瓷微珠与改性硅酸锆微球,两类空心微珠和微球通过封闭孔腔、多级粒径填充和界面热阻效应,降低水泥石连续固相导热通道。让材料同时兼具高温稳定性、耐蚀性与极低导热率,有效降低了热应力开裂的风险。
Smart Images

Figure CN122916501A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of cementing materials for oil and gas field development, specifically to a composite admixture for geothermal well cementing and its preparation method. Background Technology
[0002] The core technology for current hot dry rock geothermal extraction is CO2-EGS, which uses supercritical CO2 as the heat exchange medium. Compared with traditional water-based media, it significantly improves heat exchange efficiency. However, its cementing sheaths are subjected to extreme conditions of high temperature, high pressure, and geothermal fluid scouring for extended periods. Under these conditions, traditional cementing is prone to carbonization corrosion, leading to increased porosity, reduced strength, and a significant increase in permeability. Existing CO2-resistant cementing systems mostly rely on silica fume / slag admixtures to increase the Si / Ca ratio or latex polymers to form a hydrophobic film. However, these systems suffer from insufficient insulation, limited thermal cycling durability, and persistent permeability increases even under long-term CO2 exposure. Therefore, developing an external admixture for geothermal extraction cementing with high corrosion resistance, low permeability, and low thermal conductivity is crucial for CO2-EGS geothermal development. Summary of the Invention
[0003] To address the shortcomings of existing technologies, this invention proposes a multi-dimensional synergistic protection system for CO2 corrosion-resistant cementitious admixtures. This system not only achieves long-term service stability of cement stone in high-temperature and high-CO2 environments, but also features high CO2 corrosion resistance, low thermal conductivity, and low permeability.
[0004] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first aspect of this invention provides a composite admixture for geothermal well cementing, comprising the following raw materials by weight percentage: Thermal insulation filler A: 20-30%; Thermal insulation filler B: 10-20%; Corrosion-resistant and impermeable materials: 60%.
[0005] Furthermore, the thermal insulation filler A is modified aluminosilicate hollow ceramic microspheres with a particle size of 100~150μm and an apparent thermal conductivity of ≤0.1W / (m·K); The preparation method of modified aluminosilicate hollow ceramic microspheres is as follows: Step 1: Select aluminosilicate hollow ceramic microspheres and sieve them to obtain particles of 100-150 μm size; add the sieved hollow ceramic microspheres to deionized water, stir for 10-15 min, let stand for 5 min, collect the floating and suspended particles, and then dry them at 105℃ for 2 h. Step 2: Add the dried hollow ceramic microspheres to a 0.5-1.0 mol / L hydrochloric acid solution for acid washing, with a liquid-to-solid ratio of 8-10 mL / g, and stir at 60℃ for 1 h; after acid washing, wash with deionized water until the pH of the filtrate is 6.5-7.5, and then dry at 105℃ for 2 h; Step 3: Prepare a silica sol with a mass fraction of 8-12%, adjust it with ethanol solution to form a silica sol dispersion with an ethanol:water volume ratio of 1:1, and add the hollow ceramic microspheres treated in Step 2. The liquid-solid ratio is 5-8 mL / g. Stir at 300-500 rpm for 30 min, then ultrasonically disperse for 15-20 min, and then vacuum impregnate for 30-60 min. After removal, filter, dry at 80℃ for 1 h, then dry at 120℃ for 2 h, and calcine at 800℃ under an argon atmosphere for 1.5 h to obtain modified aluminosilicate hollow ceramic microspheres.
[0006] Furthermore, the thermal insulation filler B is modified zirconium silicate hollow microspheres with a particle size of 30~80μm, a wall thickness of 5~10μm, and an apparent thermal conductivity of ≤0.08W / (m·K); The preparation method of modified zirconium silicate hollow microspheres is as follows: Using glucose as a carbon template, glucose was first dissolved in deionized water to prepare a 50 g / L glucose aqueous solution, and then anhydrous ethanol was added to prepare an ethanol-glucose aqueous solution with a volume ratio of ethanol:water of 2:3. In an ethanol-glucose aqueous solution, zirconium oxychloride and tetraethyl orthosilicate are added at a Zr:Si molar ratio of 1:1 to increase the Zr concentration in the ethanol-glucose aqueous solution. 4+ The concentration was 0.10 mol / L. Urea was added as a precipitant at a urea:Zr molar ratio of 3:1, and the mixture was stirred for another 30 min to obtain the reaction solution. The reaction solution was transferred to a polytetrafluoroethylene-lined hydrothermal reactor and hydrothermally reacted at 180°C for 12 hours to obtain carbon spheres@zirconium silicon oxide precursor. After washing and drying, the carbon spheres@zirconium silicon oxide precursor were heated to 600℃ at 3℃ / min and held for 2 h in air to remove the carbon template, and then heated to 1200℃ and held for 3 h to obtain modified zirconium silicate hollow microspheres.
[0007] Furthermore, the corrosion-resistant and impermeable material is composed of functional fillers, self-responsive repair materials, and corrosion-resistant reinforcing materials mixed in a mass ratio of 5:2:3. The specific preparation method is as follows: Weigh the functional filler, self-responsive repair material, and corrosion-resistant reinforcing material according to the mass ratio; add the functional filler to a dry powder mixer and stir at 400 rpm for 10 minutes to mix evenly; then add the self-responsive repair material and corrosion-resistant reinforcing material, and continue stirring for 5 minutes to mix evenly to obtain the corrosion-resistant and impermeable material.
[0008] Furthermore, the functional filler is a mixture of lithium extraction slag under pressure with nitric acid, asbestos tailings, and calcium sulfoaluminate in a mass ratio of 6:2:1. The nitric acid pressure lithium extraction slag contains SiO2 content >70%, Al2O3 content >20%, and the median particle size of the nitric acid pressure lithium extraction slag is 1~20 μm; The asbestos tailings were heat-treated at 1200℃, with SiO2 content >45%, MgO content >30%, and median particle size of 1~20 μm.
[0009] Furthermore, the self-responsive repair material is KH2PO4 microcapsules with a particle size of 20~50μm and a capsule shell thickness of 1~5μm. The specific preparation method is as follows: (1) Dissolve KH2PO4 in deionized water to form a solution A with a KH2PO4 saturation of 0.9, and obtain core material grains after spray drying; (2) Mix diethylaminoethyl methacrylate monomer (30% by mass of core material grains) and methylenebisacrylamide crosslinking agent (1.2 mol% by molar amount of diethylaminoethyl methacrylate monomer) evenly to obtain monomer phase; Sodium dodecyl sulfate was dissolved in deionized water to prepare an aqueous solution with a sodium dodecyl sulfate mass fraction of 0.2-0.5%. Initiator K2S2O8, accounting for 0.6% of the mass of the above diethylaminoethyl methacrylate monomer, was added, stirred and dissolved, and the pH was adjusted to 7.0 to obtain the aqueous phase. Add KH2PO4 to the aqueous phase to achieve a KH2PO4 saturation of 0.8~0.9. The monomer phase was slowly added to the aqueous phase at a volume ratio of 9:1. The mixture was dispersed at 800-1000 rpm for 10 min to emulsify and obtain solution B. Then the stirring speed was reduced to 350-450 rpm. (3) Add core material grains to solution B, the mass ratio of solution B to core material grains is 12:1, stir evenly, and purge with nitrogen for 30 min to remove oxygen; heat to 65°C and maintain the temperature for 4 h for polymerization reaction. (4) After the polymerization reaction is completed, the reaction system is cooled to room temperature, the microcapsules are separated by filtration, washed once with an aqueous solution of KH2PO4 with a saturation of 0.8-0.9, washed once with ethanol, and then vacuum dried at 45°C until the water content is <2% to obtain dried microcapsules; (5) Dissolve KH550 silane coupling agent in ethanol to prepare an ethanol solution with a KH550 mass fraction of 1.0%, add dried microcapsules at a liquid-to-solid ratio of 10 mL / g, stir at room temperature for 40 min for pretreatment, filter and separate, and vacuum dry at 50°C for 2 h to obtain pretreated microcapsules. (6) Disperse the pretreated microcapsules in anhydrous ethanol, control the mass ratio of microcapsules to anhydrous ethanol to be 1:9, and disperse evenly under mechanical stirring at 300 rpm to obtain a microcapsule dispersion. (7) Add 20% of the dry weight of the microcapsules of tetraethyl orthosilicate and 35% of the dry weight of the microcapsules of deionized water to the microcapsule dispersion, adjust the pH to 9-10 with ammonia water, and stir at 300-500 rpm for 100 min at 30°C to hydrolyze and condense the tetraethyl orthosilicate to generate silica and coat the surface of the microcapsules; after the reaction is completed, filter and separate, wash twice with ethanol, and vacuum dry at 45°C to obtain KH2PO4 microcapsules with silica coating.
[0010] Furthermore, the corrosion-resistant reinforcing material is a mixture of fluorapatite-supported lanthanum aminotrimethylphosphonate chelate and nanoporous silica-supported active magnesium oxide powder in a mass ratio of 3:2.
[0011] Furthermore, the fluorapatite-supported lanthanum aminotrimethylphosphonate chelate was prepared using a method comprising the following steps: Fluorapatite with a particle size of 120 nm was dispersed in deionized water to prepare a suspension A with a fluorapatite mass fraction of 8%. Add aminotrimethylphosphonic acid (35% of the mass of fluorapatite) to suspension A, adjust the pH to 5-6, and stir at room temperature for 30 min to form suspension B. Lanthanum nitrate hexahydrate, in an amount equal to that of aminotrimethylphosphonic acid, was added to suspension B. The mixture was heated to 60°C and stirred for 2 hours to form suspension C. The suspension C was filtered to separate the solid product; the solid product was washed three times with deionized water, and the washed solid product was vacuum dried at 80°C and then air-jet pulverized to 200 mesh to obtain the fluorapatite-supported lanthanum aminotrimethylphosphonic acid chelate.
[0012] Furthermore, the nanoporous silica-supported active magnesium oxide powder is prepared using a method comprising the following steps: Mesoporous silica with a pore size of 25 nm was dispersed in anhydrous ethanol, and the mass ratio of mesoporous silica to anhydrous ethanol was controlled at 1:9 to obtain a mesoporous silica dispersion. Add 30% by mass of active magnesium oxide to the mesoporous silica dispersion to obtain a mixture with a particle size of <20 nm for the active magnesium oxide. The mixture was ultrasonically dispersed for 30 min to uniformly disperse and load the active magnesium oxide onto the pores and surface of the mesoporous silica, thus obtaining a loaded suspension. The loaded suspension was rotary evaporated to remove the anhydrous ethanol solvent, resulting in a loaded solid powder. The solid powder was dried in an inert atmosphere at 120°C to obtain nanoporous silica-supported active magnesium oxide powder.
[0013] The second aspect of this invention provides a method for preparing the above-mentioned composite admixture for geothermal well cementing, comprising the following steps: Weigh each raw material according to the weight percentage, add thermal insulation filler A, thermal insulation filler B and corrosion-resistant and impermeable material into the powder mixer, stir at 400 rpm for 5 minutes to mix evenly, and obtain the geothermal well cementing composite admixture.
[0014] The functional fillers are pretreated before use: the lithium extraction slag from nitric acid pressure and the asbestos tailings are crushed to a median particle size of 1~20 μm, and the asbestos tailings are preheated at 1200℃.
[0015] This invention primarily utilizes corrosion-resistant and impermeable materials to achieve multi-component synergistic resistance to CO2 corrosion, the mechanism of which is as follows: The nitrate-pressurized lithium extraction slag and asbestos tailings in the functional filler are rich in active silica-alumina components (SiO2, Al2O3), which can undergo a secondary hydration reaction with the cement hydration product Ca(OH)2 to generate CSH gel with a low calcium-to-silicon ratio. This reduces the free Ca in the cement stone. 2+ The concentration of calcium sulfoaluminate decreases the substrate that reacts with CO2, while simultaneously refining the pore structure and cutting off the rapid diffusion channels of CO2. At the same time, the early hydration of calcium sulfoaluminate to form ettringite further increases the matrix density, buying time for subsequent chemical defense.
[0016] When CO2 breaches the physical barrier and the outer shell of the self-responsive repair material (KH2PO4 microcapsules), causing a drop in local pH, the polymer inner shell of the KH2PO4 microcapsules responds. This shell is polymerized from diethylaminoethyl methacrylate, and its side chains contain tertiary amines. Under the normal alkaline environment of cement stone (pH≈12~13), the polymer is in a contracted and compacted state; when the pH drops to the acidic range, the tertiary amines protonate, the polymer chains change from a hydrophobic state to a hydrophilic state, the shell swells, permeability increases, and may even rupture, thereby promoting the slow release of KH2PO4. The released KH2PO4 rapidly reacts with the active magnesium oxide supported on nanoporous silica in the corrosion-resistant reinforcing material and the active MgO released from asbestos tailings in the functional filler, generating in situ MgKPO4·6H2O with low solubility and micro-expansion characteristics in the presence of water. This phase is chemically stable in a CO2 environment and can actively deposit at the bottlenecks of pores and microcracks to form a dense blocking network, which essentially blocks the further diffusion of CO2.
[0017] Corrosion-resistant reinforcing materials further leverage multi-scale synergistic effects: Fluoroapatite itself has extremely strong acid resistance and can serve as an inert anti-corrosion skeleton to maintain the structural integrity of cement stone; the loaded aminotrimethylphosphonic acid can chelate the Ca produced during cement hydration. 2+ This reduces the content of reactants that can be corroded by CO2; chelated lanthanum ions (La 3+ It can interact with invading CO3 2- or HCO3 - A deposition reaction occurs, generating in-situ insoluble lanthanum carbonate (La2(CO3)3), further blocking ion migration channels. In the presence of water, the active magnesium oxide supported on nanoporous silica can react with intruding CO2 to form micro-expandable magnesium carbonate (MgCO3), compensating for cement stone shrinkage. Simultaneously, it can react with KH2PO4 released from the self-responsive repair material to form MgKPO4·6H2O, creating a synergistic enhancement. Furthermore, the mesoporous silica can participate in the secondary hydration of cement, refining the hydration product grains and reducing matrix porosity.
[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention employs a multi-scale synergistic mechanism to resist CO2 corrosion, overcoming the performance limitations of traditional single-material corrosion-resistant materials, and ultimately producing a material with excellent CO2 corrosion resistance. Using solid waste as the main raw material alleviates the environmental pressure from solid waste emissions and further reduces material costs. Simultaneously, by introducing modified aluminosilicate hollow ceramic microspheres and modified zirconium silicate microspheres, these two types of hollow microspheres and microspheres reduce the continuous solid-phase thermal conductivity channels of cement stone through closed pores, multi-level particle size filling, and interfacial thermal resistance effects. This allows the material to simultaneously possess high-temperature stability, corrosion resistance, and extremely low thermal conductivity, effectively reducing the risk of thermal stress cracking.
[0019] 2. The functional filler of this invention uses nitric acid-pressurized lithium extraction slag, asbestos tailings, and calcium sulfoaluminate as functional fillers. The nitric acid-pressurized lithium extraction slag and asbestos tailings, as active silica-alumina components, undergo a secondary hydration reaction with cement hydration products, reducing the system's calcium content. 2+ Concentration inhibits CO2 reactivity; calcium sulfoaluminate provides an early structural framework and forms a stable aluminate phase in the CO2 environment. The combined effect of these three factors increases matrix density and reduces the penetration path of corrosive media.
[0020] 3. The self-responsive repair material and corrosion-resistant reinforcing material provided by this invention form a secondary dense phase MgKPO4·6H2O through a synergistic reinforcement mechanism, fundamentally hindering CO2 diffusion and blocking carbonization. When the pH of the carbonized region decreases, the self-responsive repair material slowly releases KH2PO4, which reacts with the active magnesium oxide supported on nanoporous silica and the active MgO contained in asbestos tailings in the functional filler, jointly promoting the in-situ generation of MgKPO4·6H2O. This product is stable and insoluble in water in a CO2 environment, self-growing in pores and microcracks, rapidly blocking channels and crack tips, forming a dense network, and significantly reducing matrix permeability.
[0021] 4. The corrosion-resistant reinforcing material provided by this invention improves the mechanical properties and corrosion resistance of the matrix through a multi-scale synergistic reinforcement mechanism. Fluoroapatite itself has a much higher acid resistance than conventional filler materials and can serve as an inert anti-corrosion skeleton; the loaded aminotrimethylphosphonic acid can chelate the Ca produced during cement hydration. 2+ This reduces the content of reactants that can be corroded by CO2; chelated lanthanum ions can react in situ with carbonate ions to form insoluble lanthanum carbonate, blocking pore channels. Mesoporous silica can participate in the secondary hydration of cement, refining the grains of hydration products and reducing the porosity of the matrix; on the other hand, the supported active magnesium oxide can react with intruding CO2 to form micro-expandable magnesium carbonate, and can also react with KH2PO4 released from the self-responsive repair material to form MgKPO4·6H2O, compensating for cement stone shrinkage, while simultaneously blocking corrosion channels in situ, effectively preventing the penetration of CO2 and acidic media from the formation.
[0022] 5. Under the synergistic effect of each component, the composite admixture for geothermal well cementing prepared by mixing the components in a certain proportion can not only improve the high-temperature stability, compressive strength and CO2 corrosion resistance of the well cementing system, but also reduce the thermal conductivity of the well cement stone, enhance the insulation effect of the cement stone, effectively reduce heat loss during geothermal resource extraction, and improve the development and utilization rate of geothermal resources. Attached Figure Description
[0023] Figure 1 The thermogravimetric analysis curves of Examples 1-3 and cement paste after 28 days of corrosion in the same CO2 corrosive environment are shown. Detailed Implementation
[0024] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. Obviously, the described embodiments are merely some embodiments of this invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0025] In this embodiment of the invention, the thermal insulation filler A is modified aluminosilicate hollow ceramic microspheres with a particle size of 100~150μm and an apparent thermal conductivity ≤0.1W / (m·K); The preparation method of modified aluminosilicate hollow ceramic microspheres is as follows: Step 1: Select aluminosilicate hollow ceramic microspheres and sieve them to obtain particles of 100-150 μm size; add the sieved hollow ceramic microspheres to deionized water, stir for 10-15 min, let stand for 5 min, collect the floating and suspended particles, and then dry them at 105℃ for 2 h. Step 2: Add the dried hollow ceramic microspheres to a 0.5-1.0 mol / L hydrochloric acid solution for acid washing, with a liquid-to-solid ratio of 8-10 mL / g, and stir at 60℃ for 1 h; after acid washing, wash with deionized water until the pH of the filtrate is 6.5-7.5, and then dry at 105℃ for 2 h; Step 3: Prepare a silica sol with a mass fraction of 8-12%, adjust it with ethanol solution to form a silica sol dispersion with an ethanol:water volume ratio of 1:1, and add the hollow ceramic microspheres treated in Step 2. The liquid-solid ratio is 5-8 mL / g. Stir at 300-500 rpm for 30 min, then ultrasonically disperse for 15-20 min, and then vacuum impregnate for 30-60 min. After removal, filter, dry at 80℃ for 1 h, then dry at 120℃ for 2 h, and calcine at 800℃ under an argon atmosphere for 1.5 h to obtain modified aluminosilicate hollow ceramic microspheres.
[0026] In this embodiment of the invention, the thermal insulation filler B is modified zirconium silicate hollow microspheres with a particle size of 30~80μm, a wall thickness of 5~10μm, and an apparent thermal conductivity ≤0.08W / (m·K). The preparation method of modified zirconium silicate hollow microspheres is as follows: Using glucose as a carbon template, glucose was first dissolved in deionized water to prepare a 50 g / L glucose aqueous solution, and then anhydrous ethanol was added to prepare an ethanol-glucose aqueous solution with a volume ratio of ethanol:water of 2:3. In an ethanol-glucose aqueous solution, zirconium oxychloride and tetraethyl orthosilicate are added at a Zr:Si molar ratio of 1:1 to increase the Zr concentration in the ethanol-glucose aqueous solution. 4+ The concentration was 0.10 mol / L. Urea was added as a precipitant at a urea:Zr molar ratio of 3:1, and the mixture was stirred for another 30 min to obtain the reaction solution. The reaction solution was transferred to a polytetrafluoroethylene-lined hydrothermal reactor and hydrothermally reacted at 180°C for 12 hours to obtain carbon spheres@zirconium silicon oxide precursor. After washing and drying, the carbon spheres@zirconium silicon oxide precursor were heated to 600℃ at 3℃ / min and held for 2 h in air to remove the carbon template, and then heated to 1200℃ and held for 3 h to obtain modified zirconium silicate hollow microspheres.
[0027] The corrosion-resistant and impermeable material used is composed of functional fillers, self-responsive repair materials, and corrosion-resistant reinforcing materials mixed in a mass ratio of 5:2:3. The specific preparation method is as follows: Weigh the functional filler, self-responsive repair material, and corrosion-resistant reinforcing material according to the mass ratio; add the functional filler to a dry powder mixer and stir at 400 rpm for 10 minutes to mix evenly; then add the self-responsive repair material and corrosion-resistant reinforcing material, and continue stirring for 5 minutes to mix evenly to obtain the corrosion-resistant and impermeable material.
[0028] The functional filler used is a mixture of nitric acid pressure lithium extraction slag, asbestos tailings, and calcium sulfoaluminate in a mass ratio of 6:2:1. Specifically, the nitric acid pressure lithium extraction slag contains >70% SiO2 and >20% Al2O3, with a median particle size of 1–20 μm; the asbestos tailings are heat-treated at 1200℃, containing >45% SiO2 and >30% MgO, with a median particle size of 1–20 μm; and the calcium sulfoaluminate is a commercially available product with an effective content >90% and a median particle size of 5–10 μm.
[0029] In this embodiment of the invention, the self-responsive repair material used is KH2PO4 microcapsules. The median particle size of the KH2PO4 microcapsules is 20~50 μm, and the capsule wall thickness is 1~5 μm.
[0030] KH2PO4 microcapsules were prepared using a method comprising the following steps: (1) KH2PO4 is dissolved in deionized water to form a solution A with a KH2PO4 saturation of 0.9. After spray drying (inlet 180℃ / outlet 80℃), the core material grains are obtained. (2) Mix diethylaminoethyl methacrylate monomer (30% by mass of core material grains) and methylenebisacrylamide crosslinking agent (1.2 mol% by molar amount of diethylaminoethyl methacrylate monomer) evenly to obtain monomer phase; Sodium dodecyl sulfate was dissolved in deionized water to prepare an aqueous solution with a sodium dodecyl sulfate mass fraction of 0.2-0.5%. Initiator K2S2O8, accounting for 0.6% of the mass of the above diethylaminoethyl methacrylate monomer, was added, stirred and dissolved, and the pH was adjusted to 7.0 to obtain the aqueous phase. Add KH2PO4 to the aqueous phase to achieve a KH2PO4 saturation of 0.8~0.9. The monomer phase was slowly added to the aqueous phase at a volume ratio of 9:1. The mixture was dispersed at 800-1000 rpm for 10 min to emulsify and obtain solution B. Then the stirring speed was reduced to 350-450 rpm. (3) Add core material grains to solution B, the mass ratio of solution B to core material grains is 12:1, stir evenly, and purge with nitrogen for 30 min to remove oxygen; heat to 65°C and maintain the temperature for 4 h for polymerization reaction. (4) After the polymerization reaction is completed, the reaction system is cooled to room temperature, the microcapsules are separated by filtration, washed once with an aqueous solution of KH2PO4 with a saturation of 0.8-0.9, washed once with ethanol, and then vacuum dried at 45°C until the water content is <2% to obtain dried microcapsules; (5) Dissolve KH550 silane coupling agent in ethanol to prepare an ethanol solution with a KH550 mass fraction of 1.0%, add dried microcapsules at a liquid-to-solid ratio of 10 mL / g, stir at room temperature for 40 min for pretreatment, filter and separate, and vacuum dry at 50°C for 2 h to obtain pretreated microcapsules. (6) Disperse the pretreated microcapsules in anhydrous ethanol, control the mass ratio of microcapsules to anhydrous ethanol to be 1:9, and disperse evenly under mechanical stirring at 300 rpm to obtain a microcapsule dispersion. (7) Add 20% of the dry weight of the microcapsules of tetraethyl orthosilicate and 35% of the dry weight of the microcapsules of deionized water to the microcapsule dispersion, adjust the pH to 9-10 with ammonia water, and stir at 300-500 rpm for 100 min at 30°C to hydrolyze and condense the tetraethyl orthosilicate to generate silica and coat the surface of the microcapsules; after the reaction is completed, filter and separate, wash twice with ethanol, and vacuum dry at 45°C to obtain KH2PO4 microcapsules with silica coating.
[0031] In this embodiment of the invention, the corrosion-resistant reinforcing material used is a mixture of fluorapatite-supported lanthanum aminotrimethylphosphonate chelate and nanoporous silica-supported active magnesium oxide powder in a mass ratio of 3:2.
[0032] The fluorapatite-supported lanthanum aminotrimethylphosphonate chelate was prepared using a method comprising the following steps: Fluorapatite with a particle size of 120 nm was dispersed in deionized water to prepare a suspension A with a fluorapatite mass fraction of 8%. Add aminotrimethylphosphonic acid (35% of the mass of fluorapatite) to suspension A, adjust the pH to 5-6, and stir at room temperature for 30 min to form suspension B. Lanthanum nitrate hexahydrate, in an amount equal to that of aminotrimethylphosphonic acid, was added to suspension B. The mixture was heated to 60°C and stirred for 2 hours to form suspension C. The suspension C was filtered to separate the solid product; the solid product was washed three times with deionized water, and the washed solid product was vacuum dried at 80°C and then air-jet pulverized to 200 mesh to obtain the fluorapatite-supported lanthanum aminotrimethylphosphonic acid chelate.
[0033] Nanoporous silica-supported active magnesium oxide powder is prepared by a method including the following steps: Mesoporous silica with a pore size of 25 nm was dispersed in anhydrous ethanol, and the mass ratio of mesoporous silica to anhydrous ethanol was controlled at 1:9 to obtain a mesoporous silica dispersion. Add 30% by mass of active magnesium oxide to the mesoporous silica dispersion to obtain a mixture with a particle size of active magnesium oxide <20 nm. The mixture was ultrasonically dispersed for 30 min to uniformly disperse and load the active magnesium oxide onto the pores and surface of the mesoporous silica, thus obtaining a loaded suspension. The loaded suspension was rotary evaporated to remove the anhydrous ethanol solvent, resulting in a loaded solid powder. The solid powder was dried in an inert atmosphere at 120°C to obtain nanoporous silica-supported active magnesium oxide powder.
[0034] In this embodiment of the invention, the preparation method of the composite admixture for geothermal well cementing is as follows: Weigh each raw material according to the weight percentage, add thermal insulation filler A, thermal insulation filler B and corrosion-resistant and impermeable material into the powder mixer, stir at 400 rpm for 5 minutes to mix evenly, and obtain the geothermal well cementing composite admixture.
[0035] Example 1, as a preferred embodiment of the present invention, provides a composite admixture for geothermal well cementing, the composition of which is as follows: Thermal insulation filler A: 20%; Thermal insulation filler B: 20%; Corrosion-resistant and impermeable materials: 60%.
[0036] Example 2, as a preferred embodiment of the present invention, provides a composite admixture for geothermal well cementing, the composition of which is as follows: Thermal insulation filler A: 30%; Thermal insulation filler B: 10%; Corrosion-resistant and impermeable materials: 60%.
[0037] Example 3, as a preferred embodiment of the present invention, provides a composite admixture for geothermal well cementing, the composition of which is as follows (by weight percentage): Thermal insulation filler A: 25%; Thermal insulation filler B: 15%; Corrosion-resistant and impermeable materials: 60%.
[0038] Comparative Example 1 differs from the geothermal well cementing composite admixture in Example 1 in that it does not contain thermal insulation filler B. That is, its raw material composition by mass ratio is: thermal insulation filler A: corrosion-resistant and impermeable material 20%: 60%, and all other conditions are the same.
[0039] Comparative Example 2: The control material of this comparative example differs from the geothermal well cementing composite admixture of Example 1 in that it does not contain self-responsive repair material, while all other conditions are the same.
[0040] Comparative Example 3 differs from the geothermal well cementing composite admixture in Example 1 in that it does not contain corrosion-resistant reinforcing materials. That is, its raw material composition by mass ratio is: thermal insulation filler A: thermal insulation filler B = 20%: 20%, and all other conditions are the same.
[0041] For the test examples, the composite admixtures for geothermal well cementing from Examples 1-3, and the control material for the comparative example, were used to prepare cement slurry according to GB / T 19139 standard. The test formula (mass ratio) was: 80% Grade G oil well cement + 20% geothermal well cementing composite admixture / control material, with a water-cement ratio controlled at 0.5, to obtain the cementing slurry system. A blank control group was also set up: the cement slurry was prepared according to GB / T 19139 standard, with a formula of 100% Grade G oil well cement and a water-cement ratio of 0.5, to obtain the blank cementing slurry system.
[0042] The cement stone samples obtained from all the above systems were placed in a high-temperature and high-pressure corrosion reactor to simulate the high-temperature and high-pressure, supercritical CO2 corrosion environment of geothermal wells. The curing conditions were controlled as follows: temperature 150℃, CO2 partial pressure 5MPa, total pressure 10MPa (N2 partial pressure supplemented), and the corrosion curing cycles were set to 7 days and 28 days, respectively. After curing, performance tests were carried out sequentially: the compressive strength of the samples was tested using an NYSQ-2017 pressure testing machine; the permeability of each cement sample was determined according to the petroleum industry standard SY / T 6466-2000 "Evaluation Method for High-Temperature Resistance Performance of Cement Stone in Oil Wells"; and the thermal conductivity of the cement stone was tested using a DRE-2C thermal conductivity meter through the transient planar heat source method. The test results are shown in Table 1.
[0043] Table 1 Test Results
[0044] According to the experimental data in Table 1, after a certain corrosion period, the blank cement slurry system without the addition of geothermal well cement composite admixture (blank control, cement slurry) has low compressive strength, and the compressive strength degradation rate is greater than 39% with the extension of the curing period. In contrast, the cement slurry systems prepared in Examples 1-3 have high compressive strength, and the degradation rate is less than 7%, indicating that the geothermal well cement composite admixture of this invention can improve the temperature resistance of cement stone. Simultaneously, the permeability of Examples 1-3 is significantly lower than the blank control, indicating that this invention has excellent anti-permeability capabilities, can significantly improve the density of cement stone, and thus protect the cement stone from CO2 corrosion, exhibiting excellent corrosion resistance. Furthermore, the thermal conductivity of Examples 1-3 is much lower than that of the blank control, indicating that the geothermal well cement composite admixture of this invention has low thermal conductivity and good insulation properties. Analysis of the data from Comparative Examples 1-3 shows that the components of this invention work synergistically to enhance the temperature resistance, corrosion resistance, and insulation properties of the invention; each component is indispensable.
[0045] Cement stone samples from the cement slurry systems prepared in Examples 1-3 and the blank cement slurry system (blank control, cement slurry) were selected and placed in a high-temperature, high-pressure corrosion reactor to simulate downhole conditions. The environment was controlled as high-temperature, high-pressure, supercritical CO2 corrosion conditions: curing temperature 150℃, CO2 partial pressure 5MPa, total pressure 10MPa (nitrogen pressurization), and the corrosion curing period was set to 28 days. After curing, thermogravimetric analysis was performed on the solidified products of each system, and the results are as follows: Figure 1 As shown.
[0046] Studies have found that the characteristic product of CO2 corrosion of cementing cement is calcium carbonate. The thermal decomposition range of calcium carbonate is 600~750℃. Therefore, the degree of corrosion of the sample can be characterized by measuring the thermal weight loss of cement stone within this temperature range: the greater the weight loss within the range, the higher the content of calcium carbonate generated, and the easier the sample is to be corroded by CO2. Conversely, the smaller the weight loss, the better the resistance to CO2 corrosion.
[0047] Figure 1 The thermogravimetric analysis curves for Examples 1-3 and cement paste after 28 days of corrosion in the same CO2 corrosive environment are shown. The thermogravimetric tests were performed using a thermal analysis instrument manufactured by Netzsch Instruments GmbH, Germany, under nitrogen atmosphere protection and a heating rate of 10°C / min.
[0048] from Figure 1 It can be clearly seen that within the thermal decomposition range of calcium carbonate, the weight loss rate (change in mass loss) of the cement slurry samples in Examples 1-3 is significantly lower than that of the blank cement slurry system (blank control, cement slurry). This indicates that the CO2 corrosion degree of the samples of the present invention is lower and the corrosion resistance is far superior to that of the control samples. This directly proves that the composite admixture for geothermal well cementing developed in this invention can significantly improve the corrosion resistance of well cementing.
[0049] Based on the above performance test results, the technical solution of the present invention can effectively improve the mechanical properties, CO2 corrosion resistance and thermal insulation performance of the cement used for geothermal well cementing, and fully meet the working conditions of downhole cementing in geothermal wells.
[0050] Finally, it should be noted that the above embodiments are merely preferred embodiments of the present invention used to illustrate the technical solutions of the present invention, and are not intended to limit the invention, nor are they intended to limit the patent scope of the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention. That is to say, any changes or refinements made to the main design concept and spirit of the present invention that are not of substantial significance, but whose technical problems are still consistent with the present invention, should be included within the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention to other related technical fields are similarly included within the patent protection scope of the present invention.
Claims
1. A composite admixture for geothermal well cementing, characterized in that, Includes the following raw materials by weight percentage: Thermal insulation filler A: 20-30%; Thermal insulation filler B: 10-20%; Corrosion-resistant and impermeable materials: 60%.
2. The composite admixture for geothermal well cementing according to claim 1, characterized in that, The thermal insulation filler A is modified aluminosilicate hollow ceramic microspheres with a particle size of 100~150μm and an apparent thermal conductivity of ≤0.1W / (m·K); The preparation method of modified aluminosilicate hollow ceramic microspheres is as follows: Step 1: Select aluminosilicate hollow ceramic microspheres and sieve them to obtain particles of 100-150 μm size; add the sieved hollow ceramic microspheres to deionized water, stir for 10-15 min, let stand for 5 min, collect the floating and suspended particles, and then dry them at 105℃ for 2 h. Step 2: Add the dried hollow ceramic microspheres to a 0.5-1.0 mol / L hydrochloric acid solution for acid washing, with a liquid-to-solid ratio of 8-10 mL / g, and stir at 60℃ for 1 h; after acid washing, wash with deionized water until the pH of the filtrate is 6.5-7.5, and then dry at 105℃ for 2 h; Step 3: Prepare a silica sol with a mass fraction of 8-12%, adjust it with ethanol solution to form a silica sol dispersion with an ethanol:water volume ratio of 1:1, and add the hollow ceramic microspheres treated in Step 2. The liquid-solid ratio is 5-8 mL / g. Stir at 300-500 rpm for 30 min, then ultrasonically disperse for 15-20 min, and then vacuum impregnate for 30-60 min. After removal, filter, dry at 80℃ for 1 h, then dry at 120℃ for 2 h, and calcine at 800℃ under an argon atmosphere for 1.5 h to obtain modified aluminosilicate hollow ceramic microspheres.
3. The composite admixture for geothermal well cementing according to claim 1, characterized in that, The thermal insulation filler B is modified zirconium silicate hollow microspheres with a particle size of 30~80μm, a wall thickness of 5~10μm, and an apparent thermal conductivity of ≤0.08W / (m·K). The preparation method of modified zirconium silicate hollow microspheres is as follows: Using glucose as a carbon template, glucose was first dissolved in deionized water to prepare a 50 g / L glucose aqueous solution, and then anhydrous ethanol was added to prepare an ethanol-glucose aqueous solution with a volume ratio of ethanol:water of 2:
3. In an ethanol-glucose aqueous solution, zirconium oxychloride and tetraethyl orthosilicate are added at a Zr:Si molar ratio of 1:1 to increase the Zr concentration in the ethanol-glucose aqueous solution. 4+ The concentration was 0.10 mol / L. Urea was added as a precipitant at a urea:Zr molar ratio of 3:1, and the mixture was stirred for another 30 min to obtain the reaction solution. The reaction solution was transferred to a polytetrafluoroethylene-lined hydrothermal reactor and hydrothermally reacted at 180°C for 12 hours to obtain carbon spheres@zirconium silicon oxide precursor. After washing and drying, the carbon spheres@zirconium silicon oxide precursor were heated to 600℃ at 3℃ / min and held for 2h in air to remove the carbon template, and then heated to 1200℃ and held for 3h to obtain modified zirconium silicate hollow microspheres.
4. The composite admixture for geothermal well cementing according to claim 1, characterized in that, The corrosion-resistant and impermeable material is composed of functional fillers, self-responsive repair materials, and corrosion-resistant reinforcing materials mixed in a mass ratio of 5:2:
3. The specific preparation method is as follows: Weigh the functional filler, self-responsive repair material, and corrosion-resistant reinforcing material according to the mass ratio; add the functional filler to a dry powder mixer and stir at 400 rpm for 10 minutes to mix evenly; then add the self-responsive repair material and corrosion-resistant reinforcing material, and continue stirring for 5 minutes to mix evenly to obtain the corrosion-resistant and impermeable material.
5. The composite admixture for geothermal well cementing according to claim 4, characterized in that, The functional filler is a mixture of lithium extraction slag under pressure with nitric acid, asbestos tailings and calcium sulfoaluminate in a mass ratio of 6:2:
1. The nitric acid pressure lithium extraction slag contains SiO2 content >70%, Al2O3 content >20%, and the median particle size of the nitric acid pressure lithium extraction slag is 1~20 μm; The asbestos tailings were heat-treated at 1200℃, with SiO2 content >45%, MgO content >30%, and median particle size of 1~20 μm.
6. The composite admixture for geothermal well cementing according to claim 4, characterized in that, The self-responsive repair material is KH2PO4 microcapsules with a particle size of 20-50 μm and a capsule shell thickness of 1-5 μm. The specific preparation method is as follows: (1) Dissolve KH2PO4 in deionized water to form a solution A with a KH2PO4 saturation of 0.9, and obtain core material grains after spray drying; (2) Mix diethylaminoethyl methacrylate monomer (30% by mass of core material grains) and methylenebisacrylamide crosslinking agent (1.2 mol% by molar amount of diethylaminoethyl methacrylate monomer) evenly to obtain monomer phase; Sodium dodecyl sulfate was dissolved in deionized water to prepare an aqueous solution with a sodium dodecyl sulfate mass fraction of 0.2-0.5%. Initiator K2S2O8, accounting for 0.6% of the mass of the above diethylaminoethyl methacrylate monomer, was added, stirred and dissolved, and the pH was adjusted to 7.0 to obtain the aqueous phase. Add KH2PO4 to the aqueous phase to achieve a KH2PO4 saturation of 0.8~0.
9. The monomer phase was slowly added to the aqueous phase at a volume ratio of 9:
1. The mixture was dispersed at 800-1000 rpm for 10 minutes to emulsify and obtain solution B. Then the stirring speed was reduced to 350-450 rpm. (3) Add core material grains to solution B, the mass ratio of solution B to core material grains is 12:1, stir evenly, and purge with nitrogen for 30 min to remove oxygen; heat to 65°C and maintain the temperature for 4 h for polymerization reaction. (4) After the polymerization reaction is completed, the reaction system is cooled to room temperature, the microcapsules are separated by filtration, washed once with an aqueous solution of KH2PO4 with a saturation of 0.8-0.9, washed once with ethanol, and then vacuum dried at 45°C until the water content is <2% to obtain dried microcapsules; (5) Dissolve KH550 silane coupling agent in ethanol to prepare an ethanol solution with a KH550 mass fraction of 1.0%, add dried microcapsules at a liquid-to-solid ratio of 10 mL / g, stir at room temperature for 40 min for pretreatment, filter and separate, and vacuum dry at 50°C for 2 h to obtain pretreated microcapsules. (6) Disperse the pretreated microcapsules in anhydrous ethanol, control the mass ratio of microcapsules to anhydrous ethanol to be 1:9, and disperse evenly under mechanical stirring at 300 rpm to obtain a microcapsule dispersion. (7) Add 20% of the dry weight of the microcapsules of tetraethyl orthosilicate and 35% of the dry weight of the microcapsules of deionized water to the microcapsule dispersion, adjust the pH to 9-10 with ammonia water, and stir at 300-500 rpm for 100 min at 30°C to hydrolyze and condense the tetraethyl orthosilicate to generate silica and coat the surface of the microcapsules; after the reaction is completed, filter and separate, wash twice with ethanol, and vacuum dry at 45°C to obtain KH2PO4 microcapsules with silica coating.
7. The composite admixture for geothermal well cementing according to claim 4, characterized in that, The corrosion-resistant reinforcing material is a mixture of fluorapatite-supported lanthanum aminotrimethylphosphonic acid chelate and nanoporous silica-supported active magnesium oxide powder in a mass ratio of 3:
2.
8. The composite admixture for geothermal well cementing according to claim 7, characterized in that, The fluorapatite-supported lanthanum aminotrimethylphosphonate chelate was prepared by a method comprising the following steps: Fluorapatite with a particle size of 120 nm was dispersed in deionized water to prepare a suspension A with a fluorapatite mass fraction of 8%. Add aminotrimethylphosphonic acid (35% of the mass of fluorapatite) to suspension A, adjust the pH to 5-6, and stir at room temperature for 30 minutes to form suspension B. Lanthanum nitrate hexahydrate, in an amount equal to that of aminotrimethylphosphonic acid, was added to suspension B. The mixture was heated to 60°C and stirred for 2 hours to form suspension C. The suspension C was filtered to separate the solid product; the solid product was washed three times with deionized water, and the washed solid product was vacuum dried at 80°C and then air-jet pulverized to 200 mesh to obtain the fluorapatite-supported lanthanum aminotrimethylphosphonic acid chelate.
9. The composite admixture for geothermal well cementing according to claim 7, characterized in that, Nanoporous silica-supported active magnesium oxide powder is prepared by a method including the following steps: Mesoporous silica with a pore size of 25 nm was dispersed in anhydrous ethanol, and the mass ratio of mesoporous silica to anhydrous ethanol was controlled at 1:9 to obtain a mesoporous silica dispersion. Add 30% by mass of active magnesium oxide to the mesoporous silica dispersion to obtain a mixture with a particle size of active magnesium oxide <20 nm. The mixture was ultrasonically dispersed for 30 min to uniformly disperse and load the active magnesium oxide onto the pores and surface of the mesoporous silica, thus obtaining a loaded suspension. The loaded suspension was rotary evaporated to remove the anhydrous ethanol solvent, resulting in a loaded solid powder. The solid powder was dried in an inert atmosphere at 120°C to obtain nanoporous silica-supported active magnesium oxide powder.
10. A method for preparing a composite admixture for geothermal well cementing as described in any one of claims 1-9, characterized in that, Includes the following steps: Weigh each raw material according to the weight percentage, add thermal insulation filler A, thermal insulation filler B and corrosion-resistant and impermeable material into the powder mixer, stir at 400 rpm for 5 minutes to mix evenly, and obtain the geothermal well cementing composite admixture.